The Grasses of Madhya Pradesh - Tiwar, S. D. N. (Indian Forester, 1954)
In this paper a general description has been given of all the grasses collected from Mandla, Chanda, Bastar and a few other districts of Madhya Pradesh along with their ecology and economic importance.